Inherent mechanical properties of bilayer germanene coupled by covalent bonding. Issue 59 (25th October 2019) - Arshee, Mahmuda Raakib; Adnan, Saqeeb; Motalab, Mohammad; Bose, Pritom
Abstract : Presence of interlayer bonds in bi-layer germanene results in a distinct fracture mechanism in tensile loading and direction dependent periodic behavior in shear loading. Abstract : Germanene, a two-dimensional buckled hexagonal structure of germanium atoms, has attractive mechanical, optical, thermal and electronic features. Recently it has been reported that covalent bonding between two monolayer germanene sheets leads to the integration of intrinsic magnetism and band gap opening that makes it attractive to future nanoelectronics. In order to use the captivating features of this structure, its mechanical characterization needs to be studied. In this study, molecular dynamics simulations have been performed using optimized Tersoff potential to analyze the effect of chirality, temperature and strain rate on the uniaxial tensile properties of this structure. This study suggests that bonded bilayer germanene shows higher mechanical strength compared to monolayer germanene. Uniaxial loading in the armchair direction shows higher fracture strength and strain compared to the zigzag direction which is contrary to the monolayer germanene. It also reports that with increasing temperature, both the fracture strength and strain of the structure decrease. It has been found that at a higher strain rate, the material exhibits higher fracture strength and strain. Mechanical properties and fracture mechanisms of defected structures have also been reported below the curie temperature. Moreover, the interlayer shear characteristics of the bilayer structure have been looked into. These results will provide significant insight to the investigation of this structure as a potential nano-electronics substitute.